73=-2+3(1+4b)

Simple and best practice solution for 73=-2+3(1+4b) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 73=-2+3(1+4b) equation:



73=-2+3(1+4b)
We move all terms to the left:
73-(-2+3(1+4b))=0
We add all the numbers together, and all the variables
-(-2+3(4b+1))+73=0
We calculate terms in parentheses: -(-2+3(4b+1)), so:
-2+3(4b+1)
determiningTheFunctionDomain 3(4b+1)-2
We multiply parentheses
12b+3-2
We add all the numbers together, and all the variables
12b+1
Back to the equation:
-(12b+1)
We get rid of parentheses
-12b-1+73=0
We add all the numbers together, and all the variables
-12b+72=0
We move all terms containing b to the left, all other terms to the right
-12b=-72
b=-72/-12
b=+6

See similar equations:

| 6x-4=2x-64 | | 2x+2.5=3 | | 3a+3=4a-4 | | n-5/8=2 | | -5h=-7h−6 | | -72=4-4(-5x+4) | | 4x=-4(x=-1) | | 3(2x-5)=2x+3=1 | | -78=-6(2b+3) | | 8=n+27/6 | | -9=1+6m-m | | 6(q-72)=72 | | -3=n+3-4n | | 3y-10=2(4y-5) | | 9x-4x=24(x=18) | | 2x-11=3x-13 | | -18y-2y=26 | | -5=-a+6a | | 7x+4=10(x=2) | | 11n=2 | | 1/5(10x+20)-4=0 | | 3(x-11)=2x+5 | | 2d+44=-10 | | h/5+8=13 | | 2x2x=5 | | 5z-22=73 | | 5z−22=73 | | x^2-x=81/8 | | 0.25x-0.8=2.45-0.35x | | 2n+5n=10 | | v+116=4 | | 30=q/5 |

Equations solver categories